Analisis Kinerja Aparatur Sipil Negara dalam hal Disiplin Kerja di Kantor Kecamatan Tanjungbalai Utara Kota Tanjungbalai - Sirait, Novianti Diva Nilakrisna; Warjio, Warjio; Harahap, Dumasari; Kadir, Abdul (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2019)
The research objective is to describe the performance of the State Civil Apparatus in terms of work discipline, to describe the obstacles in improving the performance of the State Civil Apparatus in terms of discipline and to describe the efforts made in improving the performance of the State Civil Apparatus in terms of work discipline in the Tanjungbalai District Office of North Tanjungbalai City. With descriptive qualitative research methods, this type of research is descriptive qualitative by making direct observations or observations, interviews and documentation. The results of the research show that the application of disciplinary regulations within the scope of the North Tanjungbalai Sub-district office in Tanjungbalai City still implies that the regulations apply but in reality there are some things that have not been carried out optimally, there are still employees who cannot be invited to collaborate in routine Kecamatan activities and often leave offices during office hours such employee attitudes hamper service performance for the community. As for the obstacles faced in disciplinary regulations, namely the Lack of awareness of employees in carrying out their duties and responsibilities, the lack of professionalism and responsibility of Civil Servants in carrying out their duties, the lack of strict Sanctions given by the Authorized Officials and the Fading of Discipline of Regional Civil Servants.